FACTORS THAT AFFECT PARTICIPATION OF FARMERS ON THE SUCCESS OF IMPLEMENTATION OF RICE FARMING INSURANCE PROGRAM (AUTP) IN PADANG CITY : SEM-PLS ANALYSIS - Ilham Martadona; Siti Khairani Elhakim (Jurnal Hexagro, 2020)
The agricultural sector, especially the food crops sub-sector is an important sub-sector to realize food security which is a national development goal. Agricultural insurance is a solution offered by the government through the Ministry of Agriculture to overcome crop failure caused by extreme climate change, which will have an impact on national food security. The purpose of this study was to analyze factors associated with the participation of farmers in the successful implementation of the program asu warranty rice farming in the city of Padang . Data collection consists of primary and secondary data. Data collection techniques using surveys and interviews, with the number of research respondents as many as 60. Data analysis using quantitative analysis with the Structural Equation Modeling approach - martial Least Square (SEM-PLS). The results showed that the characteristics of farmers had a negative or opposite effect on the success of the AUTP program in Padang , the stronger the characteristics of farmers would reduce the success of the AUTP program . Variables that have a significant effect are the characteristics of the nut; level of education; s IKAP to change; farm experience ; and land area .Keywords: AUTP, Farmer Participation, SEM-PLS Analysis